A mística do amor em Hadewijch de Amberes e Adélia Prado: quando a união com o divino se traduz em poesia - Oliveira, Paloma do Nascimento (2020)
Two mystics separated between the time, but sharing something in common, compose the pair of women whose writing is object of this study. The medieval writer, Hadewijch of Antwerp, and the contemporary, Adélia Prado, reserve in their compositions the mystic theme of love and bring in it approaches and detachments which have been identified in the course of this research. By trying to answer questions of which aspects would have allowed this dialog that was made a comparative reflection between the lyrics of love and the mystic between both and analyzing the presence of courteous love and Christian mystic, making this the main object of this thesis. With the research methodology focused on the discussion of those theories, as with the use of comparative literature and from the stylistic theory in which we can analyze the poems, a three-part study was accomplished. In the first part theoretical aspects of the mystics are discussed, from courteous love and the junction of the following two points; as there’s been highlighted some names of women who stood out in the literature, specially in the medieval period. In the second part it’s possible to acknowledge the writing of the two mystics, following the paths, from the stylistic point of view, that each trace on their publications. In the third moment of this thesis, reuniting four topics, it was developed an analytic study of the poems inserted and adopted following the themes of nature, fear, deliverance and the body, in a comparative manner; pointing that which unites and separates them. The reading of poems has provided the conclusion in which the feminine voices, being the medieval, being contemporary, are capable of echoing, legitimate and giving visibility to the speech of any woman who’s allowed to feel, speak, love, even tough the chosen one is highest entity of the Christian community: God.